How Digital Thrift Shops Escalate Global Supply Chain Sustainability in Indonesia - Annas, Mohammad; Humairoh, Humairoh (Publisher Cv. Inara, 2023)
The intentions of the research were to explore and analyze youngsters’ behavior toward digital shopping in particular their awareness of clothing sustainability. The research also reconfirms the trends that the latest generations were able to contribute to green business sustainability in particular the way they spend on clothing and its accessories. The shopping was done digitally through youngsters’ social media networks and they simply endorse it in their feed and timeline to let their networks know what they had done related to clothing style and where they could buy it, and even they could exchange it with each other to seek the experiences. The data were collected from major forwarder logistics, transporters and couriers specifically delivered the thrift shops’ products within capital cities in Indonesia. Considering it was a new trend, the quantity was not as massive as the products shopped from the first official stores in the marketplace or e-commerce. Nevertheless, the trends were growing each month in 2022 with a growth of between 12% and 19% each month in 2022. The trends would continue growing as well as the sustainability both in clothing and supply chains.